2003
DOI: 10.1002/lsm.10140
|View full text |Cite
|
Sign up to set email alerts
|

Basic study on vibrations during tooth preparations caused by high‐speed drilling and Er:YAG laser irradiation

Abstract: These results show that the high-speed drilling causes greater tooth vibration and has a frequency spectrum near the high sensitivity of hearing compared to the Er:YAG laser. This suggests a potential factor in provoking pain and displeasure during tooth preparation. Future study to examine the relationship of pain and amount of tooth vibration will be planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 15 publications
(17 reference statements)
1
47
0
5
Order By: Relevance
“…Some studies found that laser irradiation exhibited same or even better microleakage outcome than did the conventional bur method [53][54][55] , but other studies had contradictory results 29,52) . During cavity preparation with burs, the inevitable noise, vibration, pressure, and heat caused by high-speed drilling inevitably brings much discomfort and displeasure to the patient 56,57) . Detrimental temperature increase in the pulp can cause the cells to deteriorate, leading to pulpal pain and sensitivity 56) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that laser irradiation exhibited same or even better microleakage outcome than did the conventional bur method [53][54][55] , but other studies had contradictory results 29,52) . During cavity preparation with burs, the inevitable noise, vibration, pressure, and heat caused by high-speed drilling inevitably brings much discomfort and displeasure to the patient 56,57) . Detrimental temperature increase in the pulp can cause the cells to deteriorate, leading to pulpal pain and sensitivity 56) .…”
Section: Discussionmentioning
confidence: 99%
“…According to Takamori et al laser irradiation could be hasten by two possible approaches: The first would be increased irradiation energy; but this would cause thermal damage to enamel and dentin, a discomforting vibration and simultaneous pain. 35 The second would be to increase the rate of pulse repetition. In the present study 'VSP' (very short pulse) waveform was selected in order to maintain an adequate ablation with sufficient speed.…”
Section: Pain and Discomfort (Fig 4)mentioning
confidence: 99%
“…Mean vibration speed during laser cavity preparation reaches 166 ± 28 μm/second, at a characteristic frequency of 230 Hz, whereas the air rotor induces an almost 400 times greater vibration speed than the Er:YAG laser irradiation, which causes pain and displeasure in the patient. 35 Takamori et al suggested that high-speed drilling may cause greater bone conduction than the Er:YAG laser irradiation which could possibly lead to mild headaches or discomfort. Laser produces transient anesthetic effect on the tooth by blocking nerve conduction at Na/K pump and ablating dentinal tubules.…”
Section: Pain and Discomfort (Fig 4)mentioning
confidence: 99%
“…As the tip is not in contact with the tooth surface, this method of cavity preparation is much more agreeable to the patient [6][7][8]. In addition, many other studies have reported that lasers produce a mild local anesthetic effect, which allows for shallow cavity preparations to be completed without local analgesia [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…The sight of a drill and a local anesthetic needle syringe, along with a high-pitched sound and high-frequency vibration of the dental turbine, are the significant sources for dental anxiety, which drive the expectation of dental pain [3][4][5]. Lasers have been shown to produce 400 times less vibration, than does a burr preparation [6], and achieve an improved patient experience, as evidenced by a number of pediatric studies. These findings were based upon a change to a more pleasant sound, less vibration, and to a certain degree, low-level laser therapy effect [7][8][9], which acts to provide a form of analgesia.…”
Section: Introductionmentioning
confidence: 99%